Кадровое обеспечение крестьянских хозяйств Украины как залог их инновационного развития - Kalchenko, Sergei; Popova, Tatiana Georgievna; Kibenko, Ekaterina (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2019)
The article studies the conceptual foundations of the formation of a staffing system as one of the factors for the effective development of Ukrainian farming households. It has been proved that this problem has two aspects: staffing for the agricultural sector as a whole and the effective functioning of peasant farms as a socio-economic unit. The scientific basis for the study of the modern peculiarities of farming economy was the theory of a non-hired, family-labor economy, formulated by A. V. Chayanov. This theory justifies a clear relationship between the nature of economic activity and the specifics of social processes in farming. The scientific principles of the factor-rotation concept of economic development were laid in the basis of the development of directions for the formation of a personnel support system for representatives of the agricultural sector of Ukrainian economy. This concept considers economic growth as the result of the interaction of three basic factors: “Man”, “Nature” and “Capital”. In the process of research, the interrelation between the level of education of the heads of farms and the degree of effectiveness of their functioning have been proved. The main problems of the process of training specialists for the small agricultural enterprise system are analyzed. The directions for creating a mechanism for training personnel for farming sector have been determined. The basic professional competencies for specialists working in the field of small agricultural production have been substantiated, in particular, the following competence areas have been singled out: technical-technological, economic-analytical and system management.